2022
DOI: 10.1111/sjop.12805
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to COVID‐19‐related media content and mental health during the initial outbreak of COVID‐19 in China

Abstract: Exposure to disaster‐related media content is closely related to mental health. This study aimed to explore the patterns of COVID‐19‐related media exposure and examine whether these patterns were associated with mental health. In total, 917 participants in this study completed the Media Exposure Questionnaire (MEQ), the Positive and Negative Affect Scale (PANAS), and the Depression Anxiety Stress Scale (DASS‐21). Then latent class analysis and discriminant analysis were conducted to identify the patterns of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The Positive Affect and Negative Affect Scale (PANAS) had two ten-item subscales for evaluating respondents’ positive affect and negative affect [ 25 ]. The present study utilized the Chinese version of PANAS [ 26 ], which was confirmed to be reliable and valid in many other studies [ 27 , 28 ]. Items were rated on a fivepoint scale, from 1 (almost none) to 5 (extremely much).…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…The Positive Affect and Negative Affect Scale (PANAS) had two ten-item subscales for evaluating respondents’ positive affect and negative affect [ 25 ]. The present study utilized the Chinese version of PANAS [ 26 ], which was confirmed to be reliable and valid in many other studies [ 27 , 28 ]. Items were rated on a fivepoint scale, from 1 (almost none) to 5 (extremely much).…”
Section: Methodsmentioning
confidence: 57%
“…25 The present study utilized the Chinese version of PANAS, 26 which was confirmed to be reliable and valid in many other studies. 27,28 Items were rated on a fivepoint scale, from 1 (almost none) to 5 (extremely much). Higher scores indicate higher levels of positive affect or negative affect.…”
Section: Positive and Negative Affectmentioning
confidence: 99%
“…Exploring well-being differences between four different categories of COVID-19 media exposure (ranging from slightly to highly), Liu et al (2022) found that while stress, anxiety, and depression did not differ, positive and negative affect were significantly higher in the highly exposed group compared to the other three. While seemingly contradictory, these results would suggest that individuals are engaging with this technology in a variety of ways not disconnected from the types of content they are exposed to and actively seeking out.…”
Section: User Factorsmentioning
confidence: 99%
“…Furthermore, several of these China-based contributions use data collected during the pandemic through non-representative and mostly online surveys (e.g. [24] [25] [26] [27]). Finally, there is a large and growing literature investigating the effects of the pandemic on mental health using data from several countries ([28] [29] [30] [31] [32] [33] [34] [35] [36] [37] [38] [39]).…”
Section: Introductionmentioning
confidence: 99%